Teores de macronutrientes em mudas de aceroleira (Malpighia emarginata DC.) em função da composição do substrato - Silva de Lima, Rosiane de Lourdes [UNESP]; de Siqueira, Dalmo Lopes; Weber, Olmar Baller; Cecon, Paulo Roberto (Universidade Federal de Lavras (UFLA), 2006)
The composition of substrates with different sources of organic matter is considered as a key factor to obtain seedlings of good quality. Then, this study aimed to evaluate the best source and the best quantity of organic matter that should be used in order to produce barbados cherry (Malpighia emarginata DC.) seedlings of good quality. A factorial arrangement of four (20: 80, 40: 60, 60:40 and 80:20% of organic matter: earth) by four (earthworm compost, burnt rice husk, powdered coconut husk and carnauba straw) levels was used and it was designed in randomized blocks with four replicates. The nitrogen, phosphorus, potassium and calcium content of the leaves and stems were quantified in the dry tissue. The results showed that the proportion 80% of earthworm compost: 20% of earth allowed good development of the plants and sufficient accumulation of N, P, K and Ca. Burnt rice husk, powdered coconut husk and carnauba straw have not generated seedlings of good quality.
Macronutrients content in barbados cherry seedlings as a function of sources and levels of organic matter in the substrate
Keywords: Malpighia emarginata; cutting; substrate; organic matter